DEVELOPMENT OF AL-BAROKAH COMMUNITY READING PARK (TBM) TO IMPROVE COMMUNITY READING LITERACY IN TAMANSARI VILLAGE, PULOMERAK DISTRICT: PENGEMBANGAN TAMAN BACAAN MASYARAKAT (TBM) AL-BAROKAH UNTUK MENINGKATKAN LITERASI MEMBACA MASYARAKAT DI KELURAHAN TAMANSARI KECAMATAN PULOMERAK - Rika Kartika; Rika Kurnia; Mayla Huda; Nur Kholik Hendriawan; Tri Sari Ningsih; Atikah Sari; Ayunita Sri Rahayu; Rohaliya Melani; Meilani Sutiawati; Edyan Fajar (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Reading is a source of knowledge, so the importance of reading skills that must be possessed by each individual, but the lack of public awareness in reading literacy in Tamansari Village, Pulomerak District. This community service in its implementation uses a survey method, with the targeted target being the community in Tamansari Village. The result of the implementation of this service is that it can increase reading literacy slowly for the local community, especially children. Based on the activities that have been carried out, it can be concluded that through the development of community reading parks and a good approach with the community in Tamansari Village about the benefits of reading, it can move people to start getting used to visiting Al-Barokah community reading parks and reading books